2008
DOI: 10.22358/jafs/66604/2008
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional yeast culture has specific anti-microbial properties without affecting healthy flora. Preliminary results

Abstract: The objective of this study was to perform a preliminary assessment of the potential antimicrobial effects in vitro of nutritional yeast culture (Diamond V XP™), containing Saccharomyces cerevisiae, media on which it was grown, and metabolites produced during fermentation. It was tested against Escherichia coli ATCC25922, Staphylococcus aureus ATCC25923, Candida tropicalis ATCC13803, and oral fl ora from human saliva. Serial dilutions of each microbe were mixed with either water or an aqueous extract of yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 7 publications
(8 reference statements)
0
17
0
2
Order By: Relevance
“…Brewer et al (2014) fed SCFP (SmartCare in milk and Original XPC in starter) to calves that were infected with Salmonella; they showed that fecal shedding in control calves continued 4 more days after shedding had ended in SCFP-supplemented calves. Previous research has attributed the positive changes to bioactive components in SCFP, which may inhibit colonization of the gut by pathogenic microorganisms while encouraging the growth of healthy microflora (Jensen et al, 2008a). In a companion to the current paper, Butyrivibrio genus richness as well as butyrate concentrations were higher in SCFP-supplemented calves (Xiao et al, 2016).…”
Section: Calf Healthmentioning
confidence: 57%
“…Brewer et al (2014) fed SCFP (SmartCare in milk and Original XPC in starter) to calves that were infected with Salmonella; they showed that fecal shedding in control calves continued 4 more days after shedding had ended in SCFP-supplemented calves. Previous research has attributed the positive changes to bioactive components in SCFP, which may inhibit colonization of the gut by pathogenic microorganisms while encouraging the growth of healthy microflora (Jensen et al, 2008a). In a companion to the current paper, Butyrivibrio genus richness as well as butyrate concentrations were higher in SCFP-supplemented calves (Xiao et al, 2016).…”
Section: Calf Healthmentioning
confidence: 57%
“…It is possible that XPC itself possesses antimicrobial activity. The prebiotic compound used in the present study consists of metabolites of Saccharomyces cerevisiae fermentation, and the soluble metabolites were associated with growth inhibition of Candida tropicalis and Escherichia coli in vitro, likely because of competition for nutrients (Jensen et al, 2008). Soluble compounds may also increase the composition of other members of the microbial community not considered in this study.…”
Section: Discussionmentioning
confidence: 96%
“…This lower intake of milk could be explained that calves fed control diet showed more diarrhea symptom at the same period. Components of the yeast cell wall, such as oligosaccharides, b-glucan and mannan or the many metabolites contained in yeast culture, might not only benefit local and systemic immune responses, but might also have antimicrobial activities against pathogens (Murphy et al, 2007;Jensen et al, 2008). Some studies reported that yeast cell wall components interact with immune systems, stimulating macrophage activation (Selijelid et al, 1987;Djeraba and Quere, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast cell wall products such as mannoproteins and b-glucans may improve performance and overall health by preventing pathogenic bacteria from binding to intestinal epithelial cells or by modulating immune function (Spring et al, 2000;Davis et al, 2004;Wang et al, 2008). In addition, HY contains a high amount of soluble, bioactive particles that modulate the immune system (Jensen et al, 2008). Young calves are typically challenged by a variety of microbial infections, but studies on the effects of yeast-based products on immune-related serum proteins in neonatal calves with microbial infections are not readily available in the literature.…”
Section: Introductionmentioning
confidence: 99%